Executive Remuneration in the UK and its Relevance to Corporate Governance - Korambayil, Felys (2009)
Executive remuneration and its relevance to corporate governance is a broad topic which has drawn a remarkable amount of research focus. This paper aims to provide an insightful and up-to-date complement to existing literature particularly with respect to short-term executive remuneration and corporate governance practices specifically in the UK. This study initially provides an overview of the main theoretical concepts related to executive remuneration and then examines the pay-performance link. It also attempts to observe the effect of various other determinants of total executive remuneration on a sample of fifty companies from the FTSE 100 index. The study also inspects the pay-performance relationship using various components like director base salary/fees, benefits and emoluments as well as variations of executive pay like average director remuneration and HPD remuneration.